Intraspecific isotopic niche variation in broad-snouted caiman (Caiman latirostris) - Marques, Thiago S. (2013)
Strategies to minimise intraspecific competition are common in wild animals. For example, individuals may exploit food resources at different levels of the food chain. Analyses of stable isotopes are particularly useful for confirming variations in an intraspecific niche because the chemical composition of animals tends to reflect both the food consumed and the habitats occupied by the species. However, studies using this methodology to investigate neotropical crocodilians are scarce. This study aimed to verify the existence of ontogenetic and sexual niche variation in broad-snouted caiman in a silvicultural landscape in Brazil through the use of carbon and nitrogen stable isotopes. The isotopic ratios of carbon and nitrogen were determined in claw samples collected from 24 juveniles, 8 adults, and 16 hatchlings of C. latirostris. We identified a discrete ontogenetic variation in the isotopic niche and sexual difference only for juveniles. These results may indicate differences in the exploitation resources and a consequent reduction in competition between age classes.